Liquid‐Like Ionic Conduction in Solid Lithium and Sodium Monocarba‐closo‐Decaborates Near or at Room Temperature. Issue 8 (5th February 2016) - Tang, Wan Si; Matsuo, Motoaki; Wu, Hui; Stavila, Vitalie; Zhou, Wei; Talin, Albert Alec; Soloninin, Alexei V.; Skoryunov, Roman V.; Babanova, Olga A.; Skripov, Alexander V.; Unemoto, Atsushi; Orimo, Shin‐Ichi; et al.
Abstract : Both LiCB9 H10 and NaCB9 H10 exhibit liquid‐like cationic conductivities (≥0.03 S cm −1 ) in their disordered hexagonal phases near or at room temperature. These unprecedented conductivities and favorable stabilities enabled by the large pseudoaromatic polyhedral anions render these materials in their pristine or further modified forms as promising solid electrolytes in next‐generation, power devices.